Optical Technologies Supporting 5G/6G Mobile Networks - Zbigniew Zakrzewski; Mariusz Głąbowski; Piotr Zwierzykowski; Vincenzo Eramo; Francesco Giacinto Lavacca (Photonics, 2024)
Intensively developed mobile systems and networks 5G [...]